USING SET MODEL FOR LEARNING ADDITION OF INTEGERS - Lestari, Umi Puji; Putri, Ratu Ilma Indra; Hartono, Yusuf (Journal on Mathematics Education, 2015)
This study aims to investigate how set model can help students' understanding of addition of integers in fourth grade. The study has been carried out to 23 students and a teacher of IVC SD Iba Palembang in January 2015. This study is a design research that also promotes PMRI as the underlying design context and activity. Results showed that the use of set models that is packaged in activity of recording of financial transactions in two color chips and card game can help students to understand the concept of zero pair, addition with the same colored chips, and cancellation strategy.